(untitled) (Al-Aasar, 2025)
Holy Quran is the source of all sciences and arts. Allah Ta’ala has ordered man to be thoughtful and considerate in his subjects. The Holy Quran was translated into different languages. Each translation of the Quran has unique characteristics. "Irfan al-Qur’an" is the translation of the Qur’an which is adorned with numerous intellectual and qualities. If the history of Urdu translations of The Holy Quran is reviewed, there is no translation of the Quran in which the scientific facts of the Quran have been presented in the guise of words. It is the merit of “Irfan al-Qur’an” that the translator has transferred these facts in Urdu language in a very intellectual and scientific manner. Editor of the Irfan Al-Qur’an Dr. Muhammad Tahir-ul-Qadri has a beautiful blend of modern and ancient sciences in his personality, which is reflected in his translation of the Quran. In this paper, the scientific distinctions of DrTahir-ul-Qadri’s translation of "Irfan Al-Qur’an" are presented.